Comprehensive epidemiological evaluation of ruminant brucellosis and associated risk factors in some Egyptian Governorates - Nesreen Allam Tantawy Allam; Mahinour Ezzeldin Abdelsalam; Hend I. Elsharkawy; Mai Mohamed Kandil; Amany Mohamed Mohamed Mohamed; Fatma Ali; Mohamed A. Gebely; Safaa Y. Nour; Doaa Sedky; Mona Ebrahim Hussien Abd El-Gawad; Hoda M. Zaki; Nazek Al-Gallas; et al. (Veterinary World)
Background and Aim: Brucellosis contributes to significant economic losses due to abortion, weak newborns, infertility, and up to 20% reductions in milk yield in carrier animals. This study aimed to estimate the prevalence of ruminant brucellosis in six Egyptian governorates. This study aimed to estimate the prevalence of ruminant brucellosis and evaluate the risk factors regarding the epidemiological status, highlighting the importance of early carrier detection for the success of control programs.